Analisis Pengaruh Rasio Hutang Terhadap Economic Value Added (EVA) - Widasari, Ela (Universitas La Tansa Mashiro, 2013)
The research was conducted to analyze the effect of debt to total assets ratio, debt to equity, inventory turnover, receivable turnover, and working capital turnover of Economic Value Added (EVA). Nonprobability sampling method based on purposive sampling. This study used the multiple linear regression analysis. The result showed that simultaneous debt to total assets ratio, debt to equity ratio, inventory turnover, receivable turnover, and working capital turnover has no effect on Economic Value Added (EVA), partially inventory turnover affect Economic Value Added (EVA), while debt to total assets ratio, debt to equity ratio, receivable turnover and working capital turnover has no effect on Economic Value Added (EVA).